JAN AMOS KOMEŃSKI (1592-1670) JAKO PRZEDSTAWICIEL NOWOŻYTNEJ FILOZOFII WYCHOWANIA - Sztobryn, Sławomir (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2019)
Entry presents the main aspects of the philosophy of education by Comenius in a synthetic form with particular emphasis on its concept of Pan-sophy and the particular role played in his religious attitude as a leader of Czech Brethren Congregation. A characteristic motif of formal philosophy of education by Comenius was a triad: the God-Nature-Man. „The correct cognition” of these three spheres constitutes a sage.